Directors’ career concerns: Evidence from proxy contests and board interlocks - Zhang, Shuran (Journal of Financial Economics, 2021)
This paper studies the disciplinary spillover effects of proxy contests on companies that share directors with target firms, that is, interlocked firms. In difference-in-differences tests, I find that interlocked firms reduce excess cash holdings, increase shareholder payouts, cut CEO compensation, and engage in less earnings management in the year after proxy contests. The effects are more pronounced when both the interlocked and target firms have a unitary board and when the interlocking director is up for election, is younger, or has shorter tenure. Overall, the evidence highlights the importance of directors’ career concerns in policy spillovers across firms with board interlocks.